Growth, leaf gas exchange and biochemical changes of oil palm (Elaeis guineensis Jacq.) seedlings as affected by iron oxide nanoparticles - Izad, Ayu Azera; Nulit, Rosimah; Che Abdullah, Che Azurahanim; Abd. Razak, A'Fifah; Teh, Hue Fang; Ibrahim, Mohd Hafiz (AIMS Press, 2019)
Currently, magnetic iron oxide nanoparticles (Fe3O4 NPs) was extensively used in industries and agriculture. However, fewer studies have been conducted on the interaction between these nanomaterials and plants. With that, the work focused on the toxicity evaluation of Fe3O4 NPs towards the growth, leaf gas exchange and biochemical of oil palm (Elaeis guineensis Jacq.). Oil palm seedlings were grown in soil and treated with different concentrations of Fe3O4 NPs (0, 800, 1600, 2400 mg/L) for 30 days of exposure. The experiment was arranged in a randomized complete block design (RCBD) replicated three times. The study revealed that Fe3O4 NPs did not affect the plant growth but significantly (p ≤ 0.05) affected the leaf gas exchange and biochemical responses. Total chlorophyll content and leaf total stomata densities of seedlings were significantly decreased with Fe3O4 NPs, in particular with the higher Fe3O4 NPs concentration. The results showed that Fe3O4 NPs negatively affected the leaf gas exchange characteristics of seedlings as compared to the control. The Fe3O4 NPs increased the production of total flavonoids, total phenolics, proline, soluble sugar and malondialdehyde (MDA) in Fe3O4 NPs-stressed seedlings leaves extracts. Correlation analysis showed that net photosynthesis rate (A) has a significant positive correlation with leaf gas exchange traits. This showed that the reduction of leaf gas exchange performance of oil palm seedlings under elevated Fe3O4 NPs concentration might be due to decreasing of A in oil palm seedlings exposed to high Fe3O4 NPs concentration. The concentration of iron (Fe) in leaves was significantly increased with Fe3O4 NPs application. In comparison to the control (0 mg/L), the Fe content in the leaves was increased by 52% when the seedlings were treated with the highest Fe3O4 NPs concentration (2400 mg/L). Overall, a high application of Fe3O4 NPs has induced plant stress, which further affected its growth and development at phenotypic and physiological levels.